IMPLEMENTASI PKG BERDASARKAN TUGAS POKOK DAN FUNGSI GURU - Yuniarti, Siska Indria; Dwikurnaningsih, Yari (Universitas Negeri Malang, 2022)
Abstract: The study is conducted to see if the teacher performance assessment instruments used over the years have accommodating teacher duties and functions at Christian primary schools 03 Eben haezer and kristen 04 Eben haezer. What problems or deficiencies on the ground are when assessing teacher performance using only government instruments. The research method used is a descriptive method with a qualitative approach. Data collection takes place through interviews and observations. Data analysis USES data reduction, data presentation, and drawing conclusions. Studies have shown that the teacher's performance assessments performed over the years are consistent with the established conditions of preparation, practice, value-giving, and reporting. The teacher's performance assessments do not include the principal and function of teachers at the Christian 03 primary school and Christian primary school 04 Eben haezer that is to be a minister of faith, an academic leader, a spiritual leader, a biblical role model, asa mentor and character educator. The assessments used over the years only use the government's teacher performance assessment instruments. School has no special instrument that assesses the principal duties and functions of the teacher, so the principal cannot judge the teacher's strengths and weaknesses based on his or her principal duties and functions. Another obstacle faced was that teachers could not immediately receive the results of the assessment because the process of processing the old and still be done concurrentlyKeywords: Teacher performance assessment; Principal teacher function Abstrak: Penelitian ini dilakukan untuk mengetahui ketepatan penggunaan instrumen PKG yang mengakomodasi tugas pokok dan fungsi guru di Sekolah Dasar Kristen 03 Eben Haezer dan Kristen 04 Eben Haezer. Permasalahan atau kekurangan apa yang dialami di lapangan ketika menilai kinerja guru dengan hanya menggunakan instrumen dari pemerintah. Metode penelitian yang digunakan adalah metode deskriptif dengan pendekatan kualitatif. Pengumpulan data dilakukan melalui wawancara dan observasi. Analisis data menggunakan reduksi data, penyajian data, dan menarik kesimpulan. Hasil penelitian menunjukkan bahwa PKG yang dilaksanakan selama ini sudah sesuai dengan ketentuan yang berlaku yaitu persiapan, pelaksanaan, pemberian nilai, dan pelaporan. PKG tidak mencakup tugas pokok dan fungsi guru di Sekolah Dasar Kristen 03 dan Sekolah Dasar Kristen 04 Eben Haezer yaitu sebagai pelayan iman, pemimpin akademik, pemimpin spiritual, model peran Alkitab, sebagai mentor dan pendidik karakter. Penilaian yang digunakan selama ini hanya menggunakan instrumen PKG dari pemerintah. Sekolah belum memiliki instrumen khusus yang menilai tugas pokok dan fungsi guru akibatnya kepala sekolah tidak dapat menilai kelebihan dan kekurangan guru berdasarkan tugas pokok dan fungsinya. Kendala lain yang dihadapi adalah guru tidak bisa segera menerima hasil penilaian karena proses pengolahan nilai yang lama dan masih dilakukan secara konvensional. Kata kunci: Implementasi; Penilaian Kinerja Guru; Tugas Pokok Fungsi Guru